Pilot reliability investigation: final report on agreement PD/28/035/ADM - Robertson, I. A. (College of Aeronautics, 1966)
The feasibility of constructing a device to give a measure of pilot reliability has been investigated. A rig to meet the proposals made by BLEU has been designed and basic circuits constructed and tested for accuracy of operation and reliability. An estimate of the materials required and the cost of construction has been made. The rig has been designed to be subject operated for twentyfour tests before requiring attention, and devices have been incorporated to indicate unserviceability and prevent operation if starting cond4 tions are not correct. Switching sequences typical of the final period of an autoland approach are demanded verbally by magnetic tape replay equipment and the performance of the subject measured. The test consists of two phases; a preparatory or "unloaded" phase, and a "loaded" phase during which the subject performs a tracking task in addition to the switching sequence. The performance of the subject is recorded on veeder counters for both phases of the test in the form of actions demanded, actions taken and actions taken during a memory period. A measure of performance of the tracking task is also given by veeder counter.